2005
DOI: 10.1016/j.ijgo.2005.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Uterine artery ligation for management of uterine fibroids

Abstract: The procedure was found to be a safe, inexpensive, and effective therapeutic option for the treatment of symptomatic uterine fibroids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 14 publications
0
10
0
1
Order By: Relevance
“…Blockage of the uterine vessels, including UAE and UVO, has shown its effectiveness as a minimally invasive treatment for symptomatic uterine leiomyomas (35)(36)(37)(38), with treatment failure rates in the range of 1%-19% (44), although some reports showed a higher clinical failure rate of 39% (45). Possible causes for treatment failure are not fully understood; they may be multifactorial (44) and may vary in individual cases (46).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blockage of the uterine vessels, including UAE and UVO, has shown its effectiveness as a minimally invasive treatment for symptomatic uterine leiomyomas (35)(36)(37)(38), with treatment failure rates in the range of 1%-19% (44), although some reports showed a higher clinical failure rate of 39% (45). Possible causes for treatment failure are not fully understood; they may be multifactorial (44) and may vary in individual cases (46).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported the use of the UVO procedure in the management of uterine fibroids (12,15,18,20,27,28,(31)(32)(33)(34), and other studies the use of the UAO procedure for the same purpose (16,21,22,25,26,29,(31)(32)(33)(34)(35)(36)(37)(38)(39). However, the differences between the two procedures, especially in terms of patient suffering and outcome, are rarely evaluated.…”
mentioning
confidence: 99%
“…In fact, the uterine vessel occlusion (which some papers call uterine artery occlusion) procedure can be further classified into 2 different strategies, based on the literature (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). One is uterine artery occlusion alone (UAO) without simultaneous blockage of the uterine vessels and the anastomotic sites between the uterine vessels and the ovarian vessels.…”
mentioning
confidence: 99%
“…The other is uterine artery occlusion with simultaneous blockage of the uterine vessels and the anastomotic sites between the uterine vessels and the ovarian vessels (UVO). Some studies have reported the use of the UVO procedure in the management of uterine fibroids (8,12,16,21) and other studies the UAO procedure for the same purpose (10,(17)(18)(19)(20)(21). Both procedures have been used successfully in the management of symptomatic fibroids (21).…”
mentioning
confidence: 99%
“…Elle peut être réalisée avec pose de clips ou par coagulation des artères utérines à leur origine au niveau de l'artère iliaque interne [62][63][64][65][66].…”
Section: Traitement Des Artères Utérines La Ligature Bilatérale Des Aunclassified